Orexin 1 receptor antagonists in compulsive behaviour and anxiety: possible therapeutic use. - Merlo-Pich, Emilio; Melotto, Sergio (Frontiers in Neuroscience, 2014)
Fifteen years after the discovery of hypocretin/orexin a large body of evidence has been collected supporting its critical role in the modulation of several regulatory physiological functions. While reduced levels of hypocretin/orexin were early on associated with narcolepsy, increased levels have been linked in recent years to pathological states of hypervigilance and, in particular, to insomnia. The filing to FDA of the dual-activity orexin receptor antagonist (DORA) suvorexant for the indication of insomnia further corroborates the robustness of such evidences. However, as excessive vigilance is also typical of anxiety and panic episodes, as well as of abstinence and craving in substance misuse disorders, in this review we briefly discuss the evidence supporting the development of hypocretin/orexin receptor 1 (OX1) antagonists for these indications. Experiments using the OX1 antagonist SB-334867 and mutant mice have involved the OX1 receptor in mediating the compulsive reinstatement of drug seeking for ethanol, nicotine, cocaine, cannabinoids and morphine. More recently, data have been generated with the novel selective OX1 antagonists GSK1059865 and ACT-335827 on behavioural and cardiovascular response to stressors and panic-inducing agents in animals. Concluding, while waiting for pharmacologic data to become available in humans, risks and benefits for the development of an OX1 receptor antagonist for Binge Eating and Anxiety Disorders are discussed.